A real-world, retrospective, observational study of dabigatran and rivaroxaban in Turkey: Elderly patients receive inappropriately low dose of rivaroxaban - Yiğiner, Ömer; Tezcan, Mehmet; Erdal, Emrah; Değirmencioğlu, Gökhan; Acar, Gürkan; Ergelen, Mehmet; Çay, Serkan; Çetin, Hande; Özçelik, Fatih; Doğan, Mehmet; Tokatlı, Alptuğ; Özmen, Namık; et al. (E-Century Publishing Corp, 2017)
Thromboembolic complications are the most important outcomes of atrial fibrillation (AF). New oral anticoagulants (NOACs) have been presented to protect non-valvular AF patients from thromboembolic complications. In this study, we aimed to evaluate effectiveness and safety of NOACs and also reveal prescribing habits of physicians, retrospectively. NOACs and their effectiveness and safety retrospectively. Patients with non-valvular AF using either rivaroxaban or dabigatran were included in the study in five different tertiary centers. Patients were identified by scanning their medication reports. Appropriate patients were called and face-to-face interviews were done. Follow-ups were carried out on the phone. 183 out of 201 identified patients, taking rivaroxaban and dabigatran, were reached. General clinical characteristics were not significantly different between drug groups. Vascular disease and persistent AF were significantly higher in the rivaroxaban group. The rate of low dose medication in the dabigatran group was higher compared to the rivaroxaban group. Average age of the patients taking low dose medication were prominently higher in both groups. Between high and low dose users of the dabigatran group, creatinine clearance (CrCl) were not differed. Among rivaroxaban group, CrCl of the low dose users were lower than of the high dose users. However, among low-dose-prescribed patients, only 6 out of 38 patients had a CrCl value in the range of 30-49 ml/min, revealing that remaining 32 patients were receiving inappropriately low rivaroxaban dose. The rate of all-cause mortality, thromboembolism and bleeding complications were not statistically significant between the medication groups. While prescribing NOAC for non-valvular AF patients, physicians seem to consider patients' ages rather than CrCl values. In terms of protecting from thromboembolism, rivaroxaban and dabigatran seem to be equally effective and safe.
WOS: 000406058200090
Keywords: Atrial Fibrillation; Dabigatran; Rivaroxaban